2015
DOI: 10.1016/j.ebiom.2015.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Astroglial Control of the Antidepressant-Like Effects of Prefrontal Cortex Deep Brain Stimulation

Abstract: Although deep brain stimulation (DBS) shows promising efficacy as a therapy for intractable depression, the neurobiological bases underlying its therapeutic action remain largely unknown. The present study was aimed at characterizing the effects of infralimbic prefrontal cortex (IL-PFC) DBS on several pre-clinical markers of the antidepressant-like response and at investigating putative non-neuronal mechanism underlying DBS action. We found that DBS induced an antidepressant-like response that was prevented by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 63 publications
4
39
0
3
Order By: Relevance
“…Previous work has also showed that IL DBS also increased slow oscillatory activities within the stimulated area (Etiévant et al. ), which is thought to reflect synchronous changes in membrane potential caused by recurrent cortical activity (Sanchez‐Vives and McCormick ; Shu et al. ).…”
Section: Discussionmentioning
confidence: 89%
“…Previous work has also showed that IL DBS also increased slow oscillatory activities within the stimulated area (Etiévant et al. ), which is thought to reflect synchronous changes in membrane potential caused by recurrent cortical activity (Sanchez‐Vives and McCormick ; Shu et al. ).…”
Section: Discussionmentioning
confidence: 89%
“…Astrocytes are also known to influence sleep pressure through release of gliotransmitters acting on neuronal adenosine A1 receptors (Florian, Vecsey, Halassa, Haydon, & Abel, ; Halassa et al, ). This information is clinically relevant as the antidepressant effects of deep‐brain stimulation appear to be dependent on astrocyte function, specifically relating to gliotransmitter release acting on A1 receptors (Etiévant et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nous avons mis en évidence, en perfusant du liquide cérébro-spinal enrichi en K + au niveau du site de stimulation, que l'action dépolarisante d'une forte concentration extracellulaire en K + semble altérer la capacité des cellules pyramidales 10 à répondre à une sollicitation à haute fréquence provoquée par une stimulation électrique à 130 Hz [9]. Ainsi, une altération de la fonction astrocytaire au niveau du site de lésion favorise l'accumulation du K + extracellulaire qui, en retour, induirait la dépolarisation de la membrane du neurone et le blocage des effets de la DBS (Figure 1).…”
Section: Référencesunclassified
“…L'ATP, considérée comme un transmetteur excitateur, est rapidement hydrolysée (après environ 200 ms) en adénosine grâce aux ectonucléotidases 3 présentes dans la fente synaptique. L'adénosine agit principalement comme un puissant inhibiteur de la transmission synaptique en activant les récepteurs adénosine 4 marqueurs précliniques de la réponse antidépressive : la DBS dans le CPF-IL induit une rapide augmentation de la neurogenèse hippocampique 7 , renverse les effets du stress sur la métaplasti-cité synaptique 8 de l'hippocampe, augmente les oscillations basses fréquences spontanées dans le CPF-IL ainsi que la fréquence de décharge des neurones sérotoninergiques et la synaptogénèse dans le raphé dorsal 9 . Or, nous avons également démontré que toutes ces modifications neuronales induites par la DBS dépendent de l'intégrité du système astrocytaire à l'endroit de la stimulation.…”
unclassified
See 1 more Smart Citation